Local Wisdom Values for Managing the Conservation Forestarea in Mountain Kaba Selupu Rejang Sub-District - Framujiastri, Novira Esa; Iskarni, Paus; Yunita, Mirna (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
This study aims to determine the local wisdom values for managing the conservation forest area in mountain Kaba Selupu Rejang Sub-District. This research is classified as a descriptive study with a qualitative approach. The selection of informants is based on snowball throwing techniques. Informants in this study consisted of village heads, traditional leaders, and supporting community members. Data collection is done through observation, documentation, and interviews with several speakers. The data analysis technique used is the analysis of Strengths, Weaknesses, Opportunities and Threats (SWOT). The results showed that the local wisdom of the community could improve the management of the mountain Kaba conservation area, which was divided into strengths, weaknesses, opportunities, and threats to the values ​​of that local wisdom.